Development of activity model of labor safety engineer using markov chains - Чернега, Юлия Сергеевна; Гогунский, Виктор Дмитриевич (Eastern-European Journal of Enterprise Technologies, 2014)
Activity model of the labor safety engineer was developed in the paper using homogeneous Markov chains with discrete states and time. Management systems in the organizational-technical systems consist of individual processes and relationships among them. Forming a rational combination of parametric and structural system characteristics will allow to create new models, methods and tools to achieve the goals of these systems. The paper examines the activities of the labor safety engineer. When constructing Markov models, decomposition of the studied system into separate states with building multiple relations among the given states is the most difficult task. In the developed oriented graph, nodes correspond to states and edges of the graph form communication interaction channels, which transmit control actions. A directed graph can be represented by an adjacency matrix. Each row of the adjacency matrix displays transitions to other system states. Due to the fact that the transition probabilities of the system are related to the process execution time, it is possible to estimate the total workload of labor safety engineer. For that, the ratio of total state probabilities by groups of processes was found. The results indicate that there is some increase in the portion of time that is given to information processes to the detriment of other job duties. Markov model allows to obtain a quantitative description of the job strain of the labor safety engineer, which is regulated by the enterprise standards.